Poster 231: Lateral Extra-articular Tenodesis Provides Supraphysiological Restraint to Internal Tibial Rotation: In vitro Biomechanical Assessment. Issue 7 (30th July 2022) - Ahsan, Zahab; Kim, Ho Bin; Marom, Niv; Jahandar, Hamidreza; Fraychineaud, Thomas; Zayyad, Zaid; Wickiewicz, Thomas; Imhauser, Carl; Pearle, Andrew; Nawabi, Danyal; Patel, Ronak
Objectives: Lateral extra-articular tenodesis (LET) reduces ACL graft failure rates two years after surgery when performed as an adjunct to ACL reconstruction (ACLR). Interestingly, previous biomechanical studies have shown that LET may reduce tibial rotation beyond that of the intact knee, while others found no such kinematic overconstraint. Parameters of ligament engagement have proven useful in characterizing the biomechanical function of the ACL and the anterolateral ligament; however, they have not been used to describe the biomechanics of LET. In this study, we compared engagement parameters (engagement point, in situ stiffness, and tissue force at peak applied load) of an LET-reconstructed knee compared to the native lateral tissues in response to an internal rotation torque at 0°, 30°, 60°, and 90° of knee flexion. Methods: Seven cadaveric knees (mean age: 39 ± 12; range: 28-54; 4 male) were mounted to a robotic manipulator. The robot applied an internal rotation torque of 5 Nm while monitoring the resulting internal tibial rotation (ITR) (in degrees). Each knee was tested following a bone-patellar tendon-bone ACL reconstruction with intact lateral tissues (consisting of the anterolateral ligament and Kaplan fibers) and after sectioning these tissues and performing LET (modified Lemaire technique). Resultant forces carried by the native lateral tissues and the LET were determined via superposition. The parameters of engagement were determined for both the native lateral tissues and the LET and compared via two-way repeated measures ANOVA (p < 0.05). Results: During an internal rotation test at full extension (0° of flexion), both the LET-reconstructed and native lateral tissues did not engage. At 30°, 60°, and 90° knee flexion, the native lateral tissues exhibited more in situ slack than the LET-reconstructed lateral tissues. Specifically, the native lateral tissues had 8° (p < 0.001), 13° (p < 0.001), and 14° (p < 0.001) more in situ slack than the LET-reconstructed lateral tissues at 30°, 60°, and 90° knee flexion, respectively. At 30° of flexion, the LET-reconstructed lateral tissues were 9° (p < 0.001) and 10° (p < 0.001) more slack than at 60° and 90° knee flexion. Across all three tested knee flexion angles (30°, 60°, and 90°), the LET-reconstructed lateral tissues had greater in situ stiffness than the native lateral tissues. The LET carried greater force at the peak applied internal rotation torque by 29 N at 30° of flexion (p = 0.006), but no statistical differences were identified at the other flexion angles. Conclusions: LET creates a supraphysiologic restraint to the native lateral tissues by engaging with less internal tibial rotation than the native lateral tissue at all flexion angles tested but full extension. The LET also carried greater force at the peak applied load and had a greater in situ stiffness at 30° of flexion than the native lateral tissues. On the whole, LET is a supraphysiological restraint to internal tibial rotation at 30° of flexion. The engagement point of LET may be modified surgically by altering the flexion angle, degree of tibial rotation at which the tenodesis is fixed, and/or the tension applied. Thus, discrepancies between previous biomechanical studies may arise from variations in one or more of these modifiable surgical parameters. Figure 1. Mean tissue force versus internal tibial rotation response of the LET and native lateral tissues with applied internal rotation torque at 0, 30, 60, and 90° of knee flexion. Whiskers represent one standard deviation. Engagement point denoted in yellow. Tissue force at peak applied internal tibial rotation torque denoted in blue.